Effect of Fungicide Spray Cover on Botrytis Cinerea Infection in Grape Bunches - Brink, J.C.; Holz, G.; Fourie, P.H. (South African Journal of Enology and Viticulture, 2017)
The effect of fungicide spray cover on Botrytis cinerea infection in grape bunches was determined. Bunches were sprayed at pea size and bunch closure with different volumes of a mixture of fenhexamid and a yellow fluorescent pigment, and the percentage fluorescent pigment coverage on pedicels was determined. Bunches were subsequently dusted with dry airborne conidia of B. cinerea in a settling tower and incubated for 24 h at high relative humidity (98%). Infection was determined by estimating the amount of B. cinerea infections on susceptible bunch parts (pedicel, receptacle and rachis) with isolations onto paraquat (herbicide) and Kerssies (B. cinerea selective) mediums. Linear regressions for the part × stage combinations of percentage B. cinerea incidence on different bunch parts were fitted on mean coverage levels. An increase in spray cover caused linear reductions in levels of B. cinerea on bunch parts. Higher B. cinerea incidences were recorded at pea size. Furthermore, higher B. cinerea incidences were found on paraquat medium for both stages, than on Kerssies medium. The information gathered from this study will be used to facilitate future determination of minimum effective coverage levels for effective B. cinerea control in grape bunches.